2022
DOI: 10.3389/fnagi.2022.968190
|View full text |Cite
|
Sign up to set email alerts
|

Identification and immune characteristics of molecular subtypes related to protein glycosylation in Alzheimer’s disease

Abstract: BackgroundProtein glycosylation has been confirmed to be involved in the pathological mechanisms of Alzheimer’s disease (AD); however, there is still a lack of systematic analysis of the immune processes mediated by protein glycosylation-related genes (PGRGs) in AD.Materials and methodsTranscriptomic data of AD patients were obtained from the Gene Expression Omnibus database and divided into training and verification datasets. The core PGRGs of the training set were identified by weighted gene co-expression ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…This correlation is clearly confirmed by our findings that ectopic expression and depletion of Mettl1 mediates adult hippocampal neurogenesis in vitro and in vivo, and improves cognitive deficits of AD, indicating that Mettl1-mediated internal m 7 G dysregulation contributes to the pathophysiology of AD. Recent research discovers the biological significance of m 7 G methylation modification in AD and develops potential predictive models to assess the risk of m 7 G subtypes and the pathological outcomes of patients with AD [29]. However, more work about the direct interplay between the internal m 7 G and AD still awaits elucidation.…”
Section: Discussionmentioning
confidence: 99%
“…This correlation is clearly confirmed by our findings that ectopic expression and depletion of Mettl1 mediates adult hippocampal neurogenesis in vitro and in vivo, and improves cognitive deficits of AD, indicating that Mettl1-mediated internal m 7 G dysregulation contributes to the pathophysiology of AD. Recent research discovers the biological significance of m 7 G methylation modification in AD and develops potential predictive models to assess the risk of m 7 G subtypes and the pathological outcomes of patients with AD [29]. However, more work about the direct interplay between the internal m 7 G and AD still awaits elucidation.…”
Section: Discussionmentioning
confidence: 99%
“…Lung Cancer: G6PD [32]; OGFRP1 [33] Reproductive System Breast Cancer: CD80, CD276 [34]; DNUFS1, LRPPRC, SLC7A11 [35] Neurodeenerative diseases MYH9, IQGAP1, ACTN4, DSTN, ACTB, MYL6, GYS1 [45] Metabolic diseases TRXR1, NFATC1 [46]…”
Section: Respiratory Systemmentioning
confidence: 99%
“…A study identified seven genes associated with disulfidptosis (MYH9, IQGAP1, ACTN4, DSTN, ACTB, MYL6, and GYS1). These genes can not only accurately assess AD subtypes, but also diagnose AD patients, providing new insights into the disease's potential pathogenesis and treatment strategies [45].…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…The glycosylation pattern of some other proteins such as TREM2 and reelin that play a role in cell signaling is also altered [ 30 , 37 ]. It has also been shown that protein glycosylation can alter immune processes, induce inflammatory responses in the brain, and affect the development of AD [ 38 ]. Glycomics studies, on the other hand, have quantitatively demonstrated changes in the frequency of overall protein glycosylation in AD brains as well as specific alterations in the glycosylation patterns of a large number of proteins and mapped glycoprotein profiles in different brain regions [ 32 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%